Climate, Settlement History, and Olive Cultivation in the Iron Age Southern Levant - Finḳelshṭayn, Yiśraʾel (Bulletin of ASOR, 2018)
In this article, we suggest a palaeo-climate reconstruction of the Iron Age based on pollen diagrams for sediment cores extracted from the center of the Sea of Galilee and from the Ze'elim ravine on the western shore of the Dead Sea. We describe three pollen zones that roughly correspond to the Iron Age I, Iron Age IIA, and Iron Age IIB-C. Pollen Zone 1 (ca. 1100-950 B.C.E.) is characterized by high arboreal and olive pollen percentages in both records, representing relatively wet climate conditions and intense olive cultivation in the regions west of the lakes. Pollen Zones 2 (ca. 950-750 B.C.E.) and 3 (ca. 750-550 B.C.E.) are typified by a profound reduction in olive cultivation. Based on Mediterranean tree pollen percentages in the Sea of Galilee record and sediment characteristics in the Ze'elim profile, climate conditions still seem to have been humid, albeit slightly less than in Pollen Zone 1. The low arboreal pollen in Pollen Zones 2 and 3 in the Ze'elim diagram is probably the result of intense human influence on the natural vegetation in the Judaean highlands. The lowest olive pollen values during the Bronze and Iron Ages were documented in both records at ca. 700 B.C.E., possibly the outcome of depopulation as a result of deportation and the succeeding abandonment of olive orchards. These and other trends discussed in the article show that climate is only one of the factors that influenced settlement processes and economic trends in antiquity.